2009
DOI: 10.1051/forest/2009062
|View full text |Cite
|
Sign up to set email alerts
|

Does ontogeny modulate irradiance-elicited plasticity of leaf traits in saplings of rain-forest tree species? A test with Dicorynia guianensis and Tachigali melinonii (Fabaceae, Caesalpinioideae)

Abstract: Keywords: plant architecture / phenotypic plasticity / photosynthetic capacity / leaf structure / tropical rain forest Abstract • Irradiance elicits a large plasticity in leaf traits, but little is known about the modulation of this plasticity by ontogeny. Interactive effects of relative irradiance and ontogeny were assessed on leaf traits for two tropical rainforest tree species: Dicorynia guianensis Amshoff and Tachigali melinonii (Harms) Barneby (Fabaceae, Caesalpinioideae).• Eleven morphological and physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
(89 reference statements)
3
19
0
Order By: Relevance
“…All individuals chosen for this study had relatively unshaded upper branches and shaded lower branches, so that had light conditions ruled GU traits, within-individual variability in these traits would have been higher than it actually was. Thus, the results sustain the idea that microclimate modulates the variations in GU traits around mean values typical of each ontogenetic stage within the species' sequence, in compliance with previous studies (Suzuki 2003;Suzuki and Suzuki 2009;Fernández et al 2007;Chaubert-Pereira et al 2009;Coste et al 2009). Thomas and Winner (2002), Ishida et al (2005), Holdaway et al (2008 and Valladares and Niinemets (2008) underlined the relevance of axis differentiation for the acclimation of plants to contrasting conditions.…”
Section: Structural Axis Differentiation In Nothofagussupporting
confidence: 91%
“…All individuals chosen for this study had relatively unshaded upper branches and shaded lower branches, so that had light conditions ruled GU traits, within-individual variability in these traits would have been higher than it actually was. Thus, the results sustain the idea that microclimate modulates the variations in GU traits around mean values typical of each ontogenetic stage within the species' sequence, in compliance with previous studies (Suzuki 2003;Suzuki and Suzuki 2009;Fernández et al 2007;Chaubert-Pereira et al 2009;Coste et al 2009). Thomas and Winner (2002), Ishida et al (2005), Holdaway et al (2008 and Valladares and Niinemets (2008) underlined the relevance of axis differentiation for the acclimation of plants to contrasting conditions.…”
Section: Structural Axis Differentiation In Nothofagussupporting
confidence: 91%
“…The relationship between V c,max and leaf age ( Fig. 1) is supported by different studies (Ackerly and Bazzaz, 1995;Coste et al, 2009;Kitajima et al, 1997;Kitajima et al, 2002) that showed a decreasing photosynthetic capacity with leaf age for tropical species. Furthermore, the relation is supported by the findings of Steppe et al (2011) and Chapin et al (2002) that reported on decreasing photosynthetic capacity with leaf age due to modifications in leaf size, thickness, density, foliar nitrogen content and lignin content in species worldwide.…”
Section: Photosynthesis Formulationsupporting
confidence: 67%
“…Plants that grow in full sun reduce investment in nitrogen for leaf chlorophyll, but increase the production of pigments involved in photoprotection, including xanthophylls (Bilger and Bjorkman 1990;Demmig-Adams 1990;Galmés et al 2007;Matsubara et al 2009). Under long-term exposure to high irradiance, carbon allocation is directed towards high leaf dry mass per unit area (LMA; Lusk et al 2008;Poorter et al 2009;Coste et al 2010), dense branching and leaf clumping (Ali and Kikuzawa 2005). Leaf inclination also tends to increase, resulting in lower radiation interception per unit leaf area when solar zenith angles are small (Falster and Westoby 2003).…”
Section: Introductionmentioning
confidence: 99%